Supreme Court condemning the contemptner - Vajpeyi, S.C. (1994)
"The author analyses proceedings of several important contempt of court cases and their outcome to highlight variations theirin and attempts to take a broader view on their possible implications"
Keywords: Public administration - India; Supreme Court - India; Supreme Court